Evaluation of the Ethiopian Grade 9 Geography Textbook - Dubale, Abey Admasu; Minale, Amare Sewnet (Ethiopian Journal of Social Sciences, 2025)
Textbooks play a critical role in the teaching and learning process as well as in quality of education. It is also important in determining course content and influencing students’ impressions of a discipline. Therefore, to make the textbook suitable for the teaching and learning process, further improvements of the textbook is necessary. Moreover, textbooks must be assessed and evaluated continuously. Textbook evaluation plays an important role by collecting data in such a way that textbooks can afford students the chance to learn from teachers and to incorporate relevant content into textbook design and development. The main purpose of this evaluation was to assess the Ethiopian grade 9, geography textbook. The study used a mixed methods research design. Both primary and secondary data were the main source of data employed by the study.  The study also used a checklist and interview as instruments of data collection. Thus, whenever syllabus and textbook are articulated, they should include all domains of objectives and the proportions across all chapters should be taken into consideration. The contents in four chapters of the grade 9 geography textbook are aligned with the aims laid down in the relevant syllabus prepared at the national level. The content included in the textbook is current. The ideas presented in the textbook are coherent. Though there are sufficient teaching aids, almost all the teaching aids available in the textbook are visual. Findings and results are depicted via tables and graphs. Weaknesses encountered in the textbook are presented with the possible solutions. It has been concluded that the assessment encouraged learns to develop only rote memorization of the subject matter, but much emphasis is not given to the development of higher-order thinking skills.   Keywords: Assessment techniques; Course content; Instructional objectives; Instructional strategies; Textbook evaluation